Tourism in the Portuguese Rural Areas - Vítor Jo\~ao Pereira Domingues Martinho (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
The tourism in the rural areas is an important contribution to the local economies and an additional income for the traditional local activities as the agricultural sector. Some traditional rural activities, as the agriculture, sometimes and in some locations are not sufficient to provide an acceptable return to their promoters. So the different forms of tourism in rural zones, as the small industry and others sectors, are important contributions to the economic activity in the rural areas. This study pretends to analyze some information and statistical data about the several forms of tourism in the Portuguese rural areas, namely tourism accommodation, rural tourism, agritourism, village tourism, country house and rural hotel. There were used data from 2004 to 2008 available in the Statistics of Portugal (INE) for the Portuguese NUTs II. These data were analyzed with econometric methods, namely, spatial econometrics and panel data analysis.
Keywords: O18; L83; C20; 330; Tourism; Portugal; Rural areas; Econometric analysis